Knowledge, attitude and practice on occupational safety and health among workers in petrochemical companies - Mukhtar, Mohd Yasir; Mat Yusof, Afzan; Md Isa, Muhammad Lokman (2020)
Petroleum, petrochemical or oil and gas industry is one of the important industrial sectors in Malaysia. The safety in the workplace is one of the vital issues that need to be taken seriously. Every worker should know about the occupational safety and health organization to protect them from any accidents and injuries. The purpose of this study was to determine the level of knowledge, attitude and practice on occupational safety and health among workers in petrochemical companies at Teluk Kalung Industrial Area, Kemaman, Terengganu. A cross-sectional study was conducted among the workers in petrochemical companies. A convenience sampling method was used to collect the data. Descriptive statistics was used to describe the levels of knowledge, attitude and practice (KAP) among the workers. Chi-square test were used to test the association between level of knowledge with level of attitude, level of knowledge with level of practice and level of attitude with level of practice. From the study, it found that there was significant association between level of knowledge with level of attitude (p=0.002), no significant association between knowledge level and practice level (p=0.386) and was no significant difference between the level of attitude and the level of practice (p=0.117). Therefore, this study found that the knowledge level can significantly affect the attitude level of the workers. Training on occupational safety and health should be held to improve their knowledge and attitude. It is recommended for other researcher to extend this study to other places with same industrial sector as there were few studies of knowledge, attitude and practice on occupational safety and health in petrochemical companies conducted.